Cardiac rehabilitation manual - Niebauer, J. (Springer, 2011)
Cardiac diseases are still the leading causes of death in industrialized countries. They induce considerable harm to survivors and often lead to severe and irreversible physical and neurological disabilities. However, a considerable amount can be done to prevent coronary artery disease or to slow the progression of the disease. Both can be achieved by tackling the panoply of modifiable risk factors, which have been identified to be amenable to lifestyle changes. Cardiac Rehabilitation Manual covers the general principals of exercise testing and training as well as nutritional and psychological support. After these fundamentals of cardiac rehabilitation have been laid out in appropriate depths, chapters follow on common cardiac diseases. Cases include symptomatic coronary artery disease with or without diabetes, myocardial infarction or revascularization, cases of heart failure in rather stable conditions, with or without cardiac devices. The book concludes with cardiac rehabilitation in patients with congenital cardiovascular diseases, valvular surgery, and peripheral arterial disease with claudication. Critically, the content is not presented in text book style, but rather taught on representative clinical cases, focusing on a particular patient and discussing the most appropriate diagnostic tools and treatment options. It is thus designed to be a practical guide for doctors ? many of whom have little direct experience in cardiac rehabilitation ? and geared to help them guide their patients through the options available to maximize their health status